Understanding the mechanism of ripening biochemistry and flavour development in brine ripened cheeses - Tekin, Ali; Hayaloglu, Ali Adnan (Elsevier Sci Ltd, 2023)
Biochemical events that start with cheese production and continue throughout ripening are directly related to flavour development in cheese. These reactions are also affected by the physical and chemical nature of the cheese. Volatile composition and related biochemical changes in brined cheeses were studied recently by using chromatographic techniques. Differences in the manufacture and ripening of brined cheeses reflect their chemical and biochemical characteristics, and hence, volatile composition. The main characteristic volatile group was carboxylic acids in the majority of brined cheeses and this was followed by ester and alcohol groups. In conclusion, the levels of salt, pH and gross chemical composition of these cheeses were determinative for the levels of volatiles in these cheeses. In the future, studies should focus on the characterisation of volatiles and aroma-active components in brine ripened cheeses affected by biochemical change and microbial ecology of the cheese. (c) 2022 Elsevier Ltd. All rights reserved.
Keywords: Feta-Type Cheese; Enzyme-Modified Cheese; Free Fatty-Acids; Volatile Compounds; Sensory Properties; Teleme Cheese; White Cheese; Scalding Temperature; Milk Pasteurization; Starter Cultures